Interactive Web-Based Modern Physics Learning Media with PjBL Model to Improve Scientific Attitudes: A Systematic Review - Aris Doyan; Susilawati; Ahmad Harjono; Syarful Annam; Muhammad Ikhsan; Nuraini Rachma Ardianti; Syamsul Hakim (Postgraduate, University of Mataram, 2025)
Scientific attitude requires mastery of processes that include science process skills, namely the ability to carry out an action concept, theory, and principle, law in the form of facts or evidence. Scientific attitude can be facilitated through learning with a Project Based Learning (PjBL) model and interactive web. This research aims to identify and analyze research trends of modern physics learning media based on interactive web using the PjBL model to improve scientific attitude. This research method is descriptive and analytical. The data used in this research was obtained from documents indexed by Google Scholar from 2015-2024 using Publish or Perish and Dimension.ai. Research procedures use PRISMA guidelines. The data analysis method uses bibliometric analysis assisted by VOS viewer software. The results of the analysis show that research trend indexed by Google Scholar from 2015 to 2024 has experienced a fluctuating increase. Where the research trend is with an increase in the number of publications every year, namely from 2015 to 2023. However, in 2024 the research trend on the modern physics learning media based on interactive web using the PjBL model to improve scientific attitude has decreased. There are many documents in the form of articles, proceedings, book chapters, edited, preprint and monograph books that discuss research about the trend. Key words that are often used in research of scientific attitude are critical thinking, scientific literacy, scientific approach, creativity, etc.